Le "tasfih" En Tunisie :scarification Et Sacralisation - Ghariani, Olfa Wali (جامعة الوادي - University of Eloued, 2016)
In this work we transgress taboos, prohibitions and sociocultural laws by revealing the secrets of the old beliefs, traditions and popular social consernant the act of censorship "tasfih". It is practical and symbolic representations magic called "Tasfih" or "R'bat" of sexuality.We apprehended the issue between the Tunisian society that is far from giving up the culture of honor "Sharaf". It is still attached to religious speech, religious design and / or traditional sexuality and attitudes of young Tunisians who swing between the desire of enjoyment and prohibition.We have also shown the impact of referring magical-mythicalcultural-religious sanctity of these practices and their representations. Résumé: Dans ce travail nous avons transgressé les tabous, les interdits et les lois socioculturelles en dévoilant les secrets des vielles croyances, les traditions populaires et les censures sociales consternant l’acte du "tasfih". Il s’agit de pratiques et représentations symboliques magiques dites “ Tasfih ” ou “ R’bât ”.Nous avons appréhendé l’enjeu entre la société tunisienne qui serait loin de renoncer à la culture de l’honneur“charâf”. Elle serait encore attachée au discours religieux, à la conception religieuse et/ou traditionnelle de la sexualité et les attitudes des jeunes tunisiens qui balancent entre l’envie de la jouissance et l’interdiction.Nous avons aussi montré l’incidence du référant magico-mythico-sacro-culturo-religieux sur ces pratiques et leurs représentations.
مقال
Keywords: "tasfih", sexuality, myth, desire, pleasure, prohibition, honor, modesty, rite, Blood, scar, node; tasfih", sexualité, mythe, désir, interdiction, honneur, pudeur, rite, sang, cicatrice, nœud